2019
DOI: 10.1103/physrevc.100.014305
|View full text |Cite
|
Sign up to set email alerts
|

α -spectroscopy studies of the new nuclides Pt165 and Hg170

Abstract: The new nuclides 165 Pt and 170 Hg were produced in the reactions 92 Mo(78 Kr, 5n) and 96 Ru(78 Kr, 4n) at bombarding energies of 418 MeV and 390 MeV, respectively. For 170 Hg an α-particle energy of E α = 7590(30) keV and half-life of t 1/2 = 0.08 +0.40 −0.04 ms were deduced, while for 165 Pt the corresponding values were 7272(14) keV and 0.26 +0.26 −0.09 ms. Comparison of the reduced α-decay widths with systematics indicates that both α decays are unhindered. Although combining the measured α-decay Q values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…decays of even-A platinum (•), mercury ( ), and lead ( ) isotopes, calculated using the Rasmussen approach [2] with data taken from Refs. [8][9][10][11][12]26,27]. The open star is the δ 2 α ( 180 Pt) calculated using the results from the present work and Ref.…”
Section: Resultsmentioning
confidence: 99%
“…decays of even-A platinum (•), mercury ( ), and lead ( ) isotopes, calculated using the Rasmussen approach [2] with data taken from Refs. [8][9][10][11][12]26,27]. The open star is the δ 2 α ( 180 Pt) calculated using the results from the present work and Ref.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent results seriously contradict this simple interpretation. Coulomb excitation studies of shape-coexisting structures in 96,98,100 Mo [24] showed that triaxiality plays an important role in this region. The problem of chirality in atomic nuclei with odd numbers of protons and neutrons has attracted a lot of attention in recent years.…”
Section: Heavy Ion Laboratory (Hil) Warsaw Polandmentioning
confidence: 99%
“…It is an excellent tool for decay spectroscopy of very proton-rich nuclei. Nuclei ranging from 45 Cr to 170 Hg have been successfully studied, including the discovery of five new isotopes [100,101]. Some of the most recent results involving MARA and JUROGAM3 are about probing triaxiality beyond the proton drip line and spectroscopy of 147 Tm.…”
Section: The Jyväskylä Accelerator Laboratory University Of Jyväskylä...mentioning
confidence: 99%
“…Five clover germanium detectors surrounding the MARA focal-plane detection system were used to detect γ rays emitted by long-lived isomers and daughters of the β decay of the implanted recoils. All detector signals were recorded by the triggerless total data readout (TDR) data acquisition system, and time stamped by a global 100 MHz clock which allowed to establish both temporal and spatial correlations between recoils and events obtained with the rest of the focal plane and JUROGAM 3 arrays [19,21].…”
Section: A Experimental Detailsmentioning
confidence: 99%